Architectures of finitude: New biomaterial practices from an ecofeminist perspective - Fernández, Natalia (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Ecofeminisms have emerged in the heat of social movements and form a diverse current of thought that explores synergies between feminisms and ecologies, from which it is affirmed that in order to sustain life, it is necessary to recognize the interdependence of life. The environmental crises have highlighted violence against women, in close relation to the violence suffered by nature, where gender and environment are intertwined under multiple, linked and comparable oppressions. In this sense, it is necessary to put in tension the non-neutrality of the constructive elements that surround us by analyzing their productive matrices within the capitalist system. Giving meaning to the field of materials engineering implies recognizing that technology is not neutral, in order to contemplate the ways of co-producing the habitat. It becomes urgent to know the environmental impact that material production generates on ecosystems. During the last decades, the development of bio-based materials has been growing. In this line, reflections are proposed about the environmental crisis articulated with gender inequality, and with experiences of new bio-based materials in the face of the need for access to habitat, as opposed to the hegemonic market logics that consider the city and housing -and therefore the materials that compose it- as a product and not a right. Thus, material developments are turning towards technologies where the sustainability of life is central, through the use of biodegradable materials, respecting the natural cycles of regeneration